High step‐up dc/dc converter using switch‐capacitor techniques and lower losses for renewable energy applications. Issue 10 (28th June 2018) - Maalandish, Mohammad; Hosseini, Seyed Hossein; Jalilzadeh, Tohid
Abstract : In this study, a non‐isolated high step‐up direct current (dc)/dc converter with a diode–capacitor is presented. To obtain high‐voltage gain, the voltage multiplier units (diode–capacitor) can be extended to n stages which are used between the phases in up section and down section of the proposed converter. By increasing the number of voltage multiplier units, the nominal value of the components decreases. Therefore, the maximum voltage value of diodes and power switches compared with the output voltage is decreased and finally, the normalised voltage of these devices will decrease, significantly. In addition, the power level of the proposed converter can be increased for different values of duty cycles and voltage multiplier units and also leads to high efficiency. To illustrate the advantages of the proposed converter, comparison results with other topologies are provided. The principle of operation at n  = 1, 2 stages, both theoretical analysis and experimental results of two prototypes in 100 and 250 W with operating at 40 kHz are provided.